Elementos clave para un modelo de aprendizaje basado en proyectos colaborativos online (ABPCL) en la Educación Superior. Issue 3 (2nd July 2020) - Unknown
ABSTRACT: Collaborative learning is a key approach to the development of teaching and learing activities. Project-based learning (PBL) is an approach that encourages the acquisition of skills by the students promoting collaboration among them, since it requires them to solve activities for the development of a specific product. There are various experiences of using this methodology, most of them applied in primary and secondary education, and the few that refer to higher education are carried out in classroom settings. This work presents a case study based on a specific course designed for the acquisition of the digital competence that combines collaborative online learning with PBL and the results obtained from its implementation are explained. The collected data show the success of its application and validates the design presented, highlighting the key elements for fostering collaboration among students.